Optical manipulation of arthropod pests and beneficials - Ben-Yakir, David (CAB International, 2020)
"This is the first comprehensive book on the use of light to manipulate insect pests. It includes information on important arthropod pests, pollinators, biocontrol agents and also medical/veterinary pests, and discusses the potential use of optical manipulation to improve the health of plants, domestic animals and humans"--